A model Notch response element detects Suppressor of Hairless-dependent molecular switch. - Furriols, M.; Bray, S. (Current Biology, 2001)
Cell-cell signaling mediated by Notch is critical during many different developmental processes for the specification or restriction of cell fates. Currently, the only known transduction pathway involves a DNA binding protein, Suppressor of Hairless [Su(H)] in Drosophila and CBF1 in mammals, and results in the direct activation of target genes. It has been proposed that in the absence of Notch, Su(H)/CBF1 acts as a repressor and is converted into an activator through interactions with the Notch intracellular domain [1--4]. Recently, we have also suggested that the activation of specific target genes requires synergy between Su(H) and other transcriptional activators [5]. Here we have designed an assay that allows us to directly test these hypotheses in vivo. Our results clearly demonstrate that Su(H) is able to function as the core of a molecular switch, repressing transcription in the absence of Notch and activating in the presence of Notch. In its capacity as an activator, Su(H) can cooperate synergistically with a DNA-bound transcription factor, Grainyhead. These interactions indicate a simple model for Notch target-gene regulation that could explain the precision of gene activation elicited by Notch signaling in different developmental fate decisions.